Akrotiri, Thera : An Architecture of Affluence 3,500 Years Old - Palybu, Klairē (Prehistory Monographs, 2005)
List of Tables in the Text; List of Figures in the Text; List of Color Plates; Preface; Acknowledgments; 1 The Volcanic Fate of Thera; 2 The Archaeologist: An Unexpected Visitor 3,500 Years Later; 3 The Settlement Pattern of Thera during the 2nd Millennium B.C.; 4 The Akrotiri Region: Landscape, Past and Present; 5 The Town; 6 The Buildings; 7 A Guided Tour through the Town; 8 A Synopsis of the Theran House Model; 9 The Art of Building: Materials and Techniques; 10 Design and Morphology; 11 Reconciling with the Wrath of Engelados; 12 Thera and Her Neighbors in a Time of Opulence; Bibliography